Reading habits and attitudes among students in secondary school : case study / Haslinda Husaini, Rafidah Abdul Aziz and Shahrom Tm Sulaiman - Husaini, Haslinda; Abdul Aziz, Rafidah; Tm Sulaiman, Shahrom (2011)
This study seeks to investigate the reading habits and attitudes among secondary school students from Sekolah Menengah Kebangsaan Tasik Puteri by using a survey research method. This school is located in Rawang, Selangor and is namely in the category of suburban school. Data were gathered from students of Form 4 and Form 5 which they are from different subject streams; art or science stream students. In the last several years, the government had implemented a lot of campaigns and programs pertaining to reading activities just to encourage people to read and make reading activities as part of their daily routine in life. Hence, it is essentials to instill the reading habits for the younger generation. In fact, it is widely acknowledged that the life-long habit of reading can be best inculcated and nurtured at an early age. However, a general observation that there is an overemphasis on study-related reading thus ignoring the recreational or free voluntary reading among them. Moreover, with increasing pressure on children to perform well in their academic, it is not surprising that students often associate books and reading with learning, schoolwork, school projects and passing examinations. The main problem of this study is the background that many factors influence reading to a student, it is important to find out the positive influences toward their reading habits and attitudes. The influences may be in the form of internal factors, such as student's attitudes or behaviour, and/or external factors, such as home, social cultural activities, school, parents and teachers. ln the past researchers that have been done by many people, parents of the students have been identified to have an influence on their children's reading habits and attitudes. The parents' factors include their background, temperament, reading habits, interests, degree of involvement toward their children's lifestyle. These may be considered as the independent variables. The effects of these variables are likely to have an impact on dependent variables such as the children's reading habits, literacy skills, temperament and their preferences or interest. Therefore this research was intended to find out the relationship between some of the variables which this could help to improve reading habits and attitudes of the students in the near future.